Manifesto for new social movements : equity, access, & empowerment - Rossatto, Cesar Augusto, 1961- (Emerald Publishing Limited : Information Age Publishing Inc, 2019)
"The world is currently witnessing the emergence of a new context for education, labor, and transformative social movements. Global flows of people, capital, and energy increasingly define the world we live in. The multinational corporation, with its pursuit of ever-cheaper sources of labor and materials and its disregard for human life, is the dominant form of economic organization, where capital can cross borders, but people can't. Affirmative action, democracy, and human rights are moving in from the margins to challenge capitalist priorities of "efficiency", i.e. exploitation. In some places, the representatives of popular movements are actually taking the reins of state power. Across the globe new progressive movements are emerging to bridge national identities and boundaries, in solidarity with transnational class, gender, and ethnic struggles"--